How to cheat a dragon's curse : the heroic misadventures of Hiccup Horrendous Haddock III - Cowell, Cressida (New York : Little, Brown, 2007)
Reluctant hero Hiccup Horrendous Haddock III must rescue his best friend, Fishlegs, from the deadly disease Vorpentitis. The only cure is rare and almost impossible to find ... a potato. But where will Hiccup find such a thing?
U
"Special Scholastic edition"--P. [4] of cover.
b
b
Keywords: Vikings -- Fiction; Dragons -- Fiction